Effect of climate on geographical distribution of influenza in Sulaimani province - ئەحمەد, شۆخان محەمەد; تالیب, جەزا تۆفیق (Sulaimani Journal for Humanities, 2019)
Climate is an important element that affects the human health. Most of the viruses and microbes that cause diseases require suitable climate for their growth and distribution in suitable temperature and moisture in addition to role of wind in transportation of viruses and microbes from place to place. The aim of this study is to diagnoses the effective of place and time which tend climate changes according to season and place whether these changes are yearly or seasonal or monthly and their relations with geographical distribution of influenza in sulaimani governorate. The author dependent upon meteorological stations and hospitals during (2009-2015) and records file of infected peoples with influenza. The quantitative and scientific analysis methods were used for analyzing the used data in this study. It was depended on a number of maps, tables and charts for giving more clarification to the reader.